2019
DOI: 10.1088/1361-6528/ab1774
|View full text |Cite
|
Sign up to set email alerts
|

Study of field emission properties of pure graphene-CNT heterostructures connected via seamless interface

Abstract: Vertically aligned carbon nanotubes (CNTs) have proven to be one of the best materials for use as an efficient field emitter. To further improve their efficiency as well as long-term use in practical devices, it is necessary to reduce the quantum resistance originating from the interface between electrode and emitters and the entanglement of the CNTs in a bundle texture. Thus, the incorporation of graphene at the bottom of CNT bundles via a seamless carbonaceous interface can easily solve this bottleneck. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 53 publications
(82 reference statements)
5
27
0
1
Order By: Relevance
“…It is hard to grow high-density CNTs on top of the bare Ni-foam using a Fe catalyst due to the diffusion of Fe in a Ni substrate with a high-temperature CVD technique without any barrier layers. Here, graphene works as an antidiffusion layer against the Fe catalyst and helps to grow CNTs via the formation of a seamless interface between graphene and CNTs. , This seamless interface not only provides a high surface area but also creates a smooth conducting electrical path for the exotic electron transfer process in the electrochemical reaction. Thereafter, electrochemically Ni was deposited (Figure S4a) uniformly on the CNT matrix (details analysis in Figure S5) followed by phosphorization to grow Ni 2 P anchored on the surface of CNT bundles, creating a 3D porous Ni-graphene-CNTs-Ni 2 P (NGCN) heterostructure (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is hard to grow high-density CNTs on top of the bare Ni-foam using a Fe catalyst due to the diffusion of Fe in a Ni substrate with a high-temperature CVD technique without any barrier layers. Here, graphene works as an antidiffusion layer against the Fe catalyst and helps to grow CNTs via the formation of a seamless interface between graphene and CNTs. , This seamless interface not only provides a high surface area but also creates a smooth conducting electrical path for the exotic electron transfer process in the electrochemical reaction. Thereafter, electrochemically Ni was deposited (Figure S4a) uniformly on the CNT matrix (details analysis in Figure S5) followed by phosphorization to grow Ni 2 P anchored on the surface of CNT bundles, creating a 3D porous Ni-graphene-CNTs-Ni 2 P (NGCN) heterostructure (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the majority of the peaks are shifted (2θ ∼ 0.03°–0.2°) because of the interfacial strain induced in the geometry and small lattice mismatch due to the formation of the heterostructure. , A similar type of observation has also been noticed in the Raman analysis of the heterostructure (Figure S9). The Raman spectra of NGCNC refer to the presence of D- (1343.42 cm –1 ), G- (1577.22 cm –1 ), and 2D- (2688.11 cm –1 ) bands, reflecting the existence of a graphene/CNTs matrix. , The D band arises due to the defect and structural disorder of the carbon matrix, which is ascribed to the A 1g mode of vibration; the G-band corresponds to the E 2g vibration mode of C–C bond stretching, and the 2D-band is the overtone of a D-band, which is a result of double resonance between the K-points in the Brillouin zone. , However, the peaks have been shifted toward a lower wavenumber as compared to Ni-Gr-CNTs, indicating the charge transfer between the carbon matrix and the metal phosphide. In addition, the increase of the I D / I G ratio from 0.85 to 1.05 in NGCNC reveals that more disorder and defects have been incorporated in the carbon matrix due to the deposition of metal phosphide on top of the Ni-Gr-CNTs heterostructure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach by Riyajuddin, 39 in which seamless pure graphene and a vertically grown CNT heterostructure (SGVCNT) was developed using thermal CVD and plasma-enhanced CVD. As the structure aligned vertical CNTs, the length and diameter were recorded to be about 55–60 µ m and 5–6 µ m. The heterostructure was placed on a non-active Si/SiO 2 substrate and checked for field emission properties.…”
Section: Electronic Applicationsmentioning
confidence: 99%
“…В последние годы одним из перспективных направлений развития исследований в области графен-УНТ соединений является получение композитных материалов с улучшенными эмиссионными характеристиками для последующего применения в качестве наноэмиттеров [49][50][51][52][53][54]. Одним из последних достижений в этой области стало экспериментальное получение методом электрофоретического осаждения гибридных пленок ОУНТ/графен, демонстрирующих максимальный эмиссионный ток величиной 80 mA с соответствующей плотностью тока 160 mA/cm 2 при напряженности электрического поля 9.6 V/µm [54].…”
Section: Introductionunclassified